2022
DOI: 10.24198/jkk.v10i2.39876
|View full text |Cite
|
Sign up to set email alerts
|

The motivation of flaming perpetrators as cyberbullying behavior in social media

Abstract: The most troubling behavior of cyberbullying is flaming on social media. Technological sophistication makes it easy for everyone to create fake accounts for negative comments to bullying activities on social media. The impact is very detrimental, especially for victims or targets. The most frequent consequences are deep trauma, fear, anxiety, lack of confidence, mental illness, and depression, and they can even motivate the victim to commit suicide. This impact is considered quite dangerous for the victim. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
1
Order By: Relevance
“…The possible impact on cyberbullying victims can be in the form of psychological disorders, such as excessive anxiety, always feeling afraid, depression, suicidal thoughts, post-traumatic stress symptoms, feeling depressed, afraid of meeting the bully, even depression and suicidal intent (12,17).…”
Section: Correlation Between Cyberbullying and The Psychological Impa...mentioning
confidence: 99%
“…The possible impact on cyberbullying victims can be in the form of psychological disorders, such as excessive anxiety, always feeling afraid, depression, suicidal thoughts, post-traumatic stress symptoms, feeling depressed, afraid of meeting the bully, even depression and suicidal intent (12,17).…”
Section: Correlation Between Cyberbullying and The Psychological Impa...mentioning
confidence: 99%
“…Based on findings (Matamoros-Fernández & Farkas, 2021) it is revealed that communication through social media not only generates positive words. There are six types of negative connotation words detected through Twitter applications, namely adjectives, nouns, verbs, animal names, foreign language curses, and adverbs (Arisanty & Wiradharma, 2022). Research findings by Chan et al (2013) suggest that through social media comments, three forms of cyberbullying can be encouraged through flaming or textual, verbal, and visual comments such as sexual comments, insults, humiliations, and taunts that affect individuals' environments.…”
Section: Theoretical Conceptmentioning
confidence: 99%
“…Kurangnya empati akan membuat seseorang dengan mudah mengambil kesimpulan terhadap situasi dan kondisi yang ada di sekitarnya, terutama pada hal-hal yang diunggah di media social (Arisanty & Wiradharma, 2022).…”
Section: Pengalaman Menjadi Korban Perundungan Mayaunclassified